Drying processes of pumpkin candied fruits in the microwave field: Studying the oscillating mode of energy supply - Paramonova V. A.; Kudryvtsev V. N. (Vestnik MGTU, 2019)
One of the modern trends in the food industry is the production of candied fruits and vegetables from various raw materials. In the process of production candied fruits are saturated with sugar, which partially improves the composition of fruit food acids, increases the shelf life of raw materials and facilitates its transportation. The aim of the research is to reveal the possibilities of intensifying the drying process of pumpkins in the production line of candied fruits by summing up microwave energy (microwave). The work is aimed at the justification and selection of technological modes of drying in the microwave field of pumpkin pieces pre-cooked in sugar syrup. To achieve this goal, analytical and experimental research methods have been used: planning of experiments, statistical analysis. During the research it has been found that the initial moisture content of the product and its pretreatment modes (blanching in the Combi oven) have a significant impact on the rate of moisture loss of the product during drying in the microwave field. Preliminary blanching of the pumpkin has been carried out in the Combi oven for 5 minutes at t = 120 °C. This mode of steam treatment allows better preservation of the capillary-porous structure of the product, while after five series of microwave energy supply (1 minute treatment, 5 minutes relaxation) a moisture level of 27.28 % has been achieved, as the remaining processing modes require a longer drying time. As a result of processing the obtained data, graphs of changes in mass, humidity and drying rate of the product during its processing have been created. The most significant indicators affecting the final properties of the product have been considered the total time of microwave processing of the product in the chamber, the total relaxation time of the product, the initial mass of the product and the limit shear stress of the product received for processing.